Pemberdayaan Masyarakat dalam Pemilahan Sampah Rumah Tangga di Kawasan Bantaran Sungai Palembang - Yuniati, Faiza; Erwin, Erwin; Shobur, Sherli; Polina, Dian Anasta; Afanda, Muhammad Daffa; Simanjuntak, Gabryella Fatima (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Household organic waste contributes significantly to total domestic waste in Indonesia, especially in riverbank communities. This community service activity was conducted in 3-4 Ulu Urban Village, Palembang, aiming to improve public awareness and behavior regarding household waste management, particularly organic waste. The participatory approach involved community members, health cadres, and Puskesmas staff through education sessions, video screenings, and demonstrations of waste sorting between organic and inorganic materials. Pre- and post-tests showed improvements in knowledge, attitudes, and practices related to waste management. Weekly monitoring over three weeks confirmed gradual changes in community behavior toward cleaner environments. The program's success was supported by the active involvement of community leaders and health workers. This initiative demonstrates that community-based and practical education is effective in promoting sustainable waste management behaviors and reducing the environmental health risks associated with poor sanitation. This program can be replicated in other riverbank areas with similar challenges.